Predictors of safety training transfer support as in-role behavior of occupational health and safety professionals - Freitas, A.C.; Silva, S.A.; Fugas, C. (European Journal of Training and Development, 2017)
Purpose The purpose of this study is to identify individual and contextual influences on in-house safety trainers’ role orientation toward the transfer of training (TT). Design/methodology/approach The authors tested a model where felt-responsibility for TT mediates the influence of job resources (i.e. autonomy, access to resources, access to information and organizational support) on trainers’ definition of their role and where training safety climate exerts a moderator effect. Data were collected from 201 Occupational Health and Safety (OHS) professionals, all in-house safety trainers, of large public and private companies. Structural equation modeling was used to test the hypotheses. Findings The model highlighted the mediating influence of felt-responsibility in the interplay between job resources and role orientation, the moderating influence of safety climate on the relationship of autonomy and organizational support on role definition, but not access to resources and access to information on role definition in the TT. Results suggest that how much safety trainers consider supporting the TT as a part of their overall role is affected by autonomy and organizational support through a sense of responsibility regarding training results, and these effects are influenced by the perceived importance of safety training to the organization. Research limitations/implications The study is cross-sectional and used self-reported data, meaning that causal inferences should be carefully drawn. Further studies should explore other sources of influence over felt-responsibility, for example, supervisors’ support for transfer, the relationship between how in-house safety trainers define their role in the transfer process and trainees’ effective application of their new knowledge and skills. Practical implications Companies should overtly signal the importance of safety training to in-house safety trainers because it will elicit, by reciprocity, a greater sense of personal responsibility and increased efforts concerning training success. Originality/value No previous research looked at how in-house trainers define their role in the TT, as well as the individual and contextual factors that influence their efforts toward the efficacy of training.